A computer algebra system approach in gene expression analysis. (2017) - Kavouras, Menelaos; Tsilika, Kyriaki; Exadactylos, Athanasios
The primary purpose of this study is to provide an immediate connection to analytics of biological functions and visualisation. We introduce a visual framework in the environment of a main computer algebra system (CAS), Mathematica, to picture variations and evolution schemes in gene expression. Our computational approach constructs snapshots for gene expression profiles, with the advantage of being selfevident, concise and clear. A variety of colours is employed, beyond the conventional heat map colours. We provide dynamic options to facilitate comparisons among treatments, several colour choices to perform reference gene selection tests and, thus reveal the variation of gene expression through time and/or among treatments, or genes. The performance of the programming techniques in selected case studies concerning genes involved in embryonic development of common sole (Solea solea), is presented. This work could assist researchers in biosciences with suggestions to specific gene expression mapping.